PERAN KELUARGA DALAM PENGELOLAAN CEMAS LANJUT USIA YANG MENGALAMI HIPERTENSI DI WILAYAH KERJA PUSKESMAS RAMPAL CELAKET KOTA MALANG (STUDI KASUS) - Lucia Retnowati; Hana Diah; Agus Setyo Utomo (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
People with hypertension are easily anxious because high blood pressure tends to require relatively long treatment, there is a risk of complications and can shorten life. Anxiety with strong intensity and negative nature can interfere with the physical and psychological state of the individual. Elderly people with hypertension who experience anxiety need a family role to be able to accept their current condition. This research is a descriptive case study with one family member as the research subject and was conducted on March 21-April 01, 2023. This studyused interview techniques, questionnaires, and triangulation in data collection. Criteria and sample are older that has informed consent, have cooperation, more than 60 years old. The data are presented in the form of a narrative and are accompanied by snippets of verbal expressions from the subjects of the study. The results showed that there was an increase in the role of the family as a supporter after being given an education. This is evidenced by an increase in questionnaire scores and statements from family and elderly interviews. The family can continue to increase knowledge and implement its role as a supporter. Elderly who have been given support are expected to manage anxiety as motivation to improve their health status.